Challenges of corporate restructuring of public companies in the Republic of Serbia - Mojsilović Milutin D.; Obradović Ljubomir M. (Tehnika, 2023)
This paper deals with restructuring of public enterprises in Serbia, focusing on the identification of challenges, as well as the analysis of all the key aspects relevant to the process of the restructuring. It points out the importance of theoretical perspectives and the state with its institutional framework in providing support and restructuring guidelines. Financial challenges and social aspects are also highlighted, as well as employee protection measures. It also deals with the influence of politics, economy and human capital on the process itself. The purpose of this paper is to provide a comprehensive insight into the challenges, implications, and both theoretical and practical sides to restructuring of public enterprises. The goal is to understand the complexity and specific details of the restructuring, while identifying all the key factors of the process-success and obstacles. A detailed study of relevant literature, research papers, articles and regulations had been conducted prior to writing this paper. Applicable restructuring theoretical models and concepts were also examined. After analysis and research, it was noticed that the restructuring of public enterprises in Serbia faces different challenges, such as: political interference, lack of financial resources, structure inflexibility, and resistance to change. The state and institutions play an important role in the process of restructuring. We emphasized the importance of adequate employee protection during restructuring and provided guidelines for achieving social justice. The results provide a starting point for further research, including those regarding specific sectors, implementing new technologies and some innovative approaches to restructuring.